PENGARUH PENERAPAN E-SPT TAHUNAN BADAN, TINGKAT PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DALAM MELAPORKAN SPT TAHUNAN BADAN - Trie Nadia Ayu Lizara; Timbul Simangunsong (Jurnal Akuntansi dan Perpajakan Jayakarta, 2021)
The Influence of the Implementation of the Annual Entity E-SPT, Understanding Taxation, Tax Awareness Awareness of Taxpayer Compliance of the corporate taxpayers in reporting as the agency annual. In this study using quantitative data types and data sources, namely primary data. Primary data were obtained from questionnaires distributed to corporate taxpayers at random, using the purposive sampling method at the West Jakarta Middle Tax Office. The number of questionnaires distributed was 100 questionnaires. The results of this study indicate that the Application of the Annual Annual E-SPT of the Agency has a significant effect on taxpayer compliance and taxpayer awareness. While Understanding Taxation has no significant effect on Taxpayer Compliance.